Sistema mecânico como sonda de uma transição de fase quântica - Santos, Jader Pereira dos (2011)
The Dicke model describes a system that contain a group of atoms coupled to a mode of electromagnetic field. One of the feature of this model is the present of second order quantum phase transition. In this work our main goal is to study the quantum phase transition present in the Dicke model through a mechanical probe. We consider that one of the mirrors in a optical cavity has the freedom to move under the effect of linear restoring force. In this conditions, the mirror couples to the cavity field via pressure radiation interaction. In the thermodynamic limit, we found that the moving mirror decouples from the cavity while in the super radiant phase it suffers the action of a resulting classical force. A remarkable feature is that the entropy of the mirror is not dynamically changed in any phase when the thermodynamic limit is taken. Consequently, the mechanical system will work as a probe to study the critical reservoir namely the Dicke system.